Building A Holistic Conceptual Framework of Corporate Social Reporting from an Islamic Perspective - Tilt, Carol Ann; Md Rahin, Nurliana (Asian Journal of Accounting Perspectives, 2015)
The corporate social reporting field, which has been mainly developed in the West, presents theories that neglect the perspective of religion, while the models of corporate social reporting in the current Islamic literature discuss Islamic ethical principles, obligations and social relation system in isolation and are unclear. This article provides a holistic conceptual model of Islamic corporate social reporting by adopting and modifying the models in the literature. Furthermore, it integrates the holistic conceptual model with an explanation of the theories that are common in the West, i.e. Stakeholder Theory and Social Contract Theory, in order to bridge the gap between Western and Islamic perspectives on corporate social reporting.